Characteristic of rain rate associated with floods during the 2021 rainy season around Jakarta and Bekasi River. Issue 1 (1st November 2022) - Lestari, S; Sapan, E G A; Sulistyowati, R; Belgaman, H A; Meliani, F; Winarno,; Hapsari, R I; Cahyaningtiyas, I F; Pianto, T A; Akbar, H I; Nurdiansyah,; Avianti, E; et al.
Abstract: The Megacity Jakarta has encountered serious floods associated with high intensity but a short-duration rainfall or low intensity with a long-duration rainfall. During the rainy season, on 4 Feb 2021, Jakarta was inundated as rainfall intensity increased. However, little is known about the meteorological factors that might contribute to this heavy rainfall. In this study, we used the 6-min X-Band Doppler radar, one-hour satellite and reanalysis data to understand the spatial distribution of rainfall and explore the background conditions that might influence the enhanced rainfall over Jakarta and Bekasi River. Other than previous studies, we found that over Jakarta, the areas receiving high rainfall are more widespread and further to the northeast ocean with an intensity of above 4.5 mm h -1 . High intensity of rainfall starts to develop in the afternoon over the inland areas at around 08-10Z (3.00-5.00 PM). Background condition shows a strong westerly wind speed crossing over Java Island, and this might initiate the development of rainfall over the region.